2018
DOI: 10.1364/ome.8.000629
|View full text |Cite
|
Sign up to set email alerts
|

High index contrast passive potassium double tungstate waveguides

Abstract: High-refractive-index-contrast potassium double tungstate waveguides have been experimentally demonstrated. A bulk KY(WO 4) 2 layer was successfully bonded onto a lower refractive index carrier using a UV curable optical adhesive and polished down to the thickness of 2.4 µm. A set of rib waveguides with ~2 μm width and 0.85 μm slab thickness were fabricated on the thin transferred KY(WO 4) 2 layer by focused-ion-beam milling. The upper-limit of the propagation losses of the fabricated waveguides is estimated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The high rare-earth ion dopant concentration achievable in crystalline host materials has allowed the demonstration of very high gain per unit length in an Yb 3 -doped KYWO 4 2 waveguide (∼935 dB∕cm at 980 nm) [28] and in an Er 3 -doped chloride silicate nanowire (∼100 dB∕cm at 1530 nm). However, such crystalline devices are difficult to fabricate [29] and to integrate onto a passive photonic platform for the development of more complex functionalities. Amorphous host materials can typically be deposited at the wafer level leading to simpler fabrication and integration schemes.…”
Section: Introductionmentioning
confidence: 99%
“…The high rare-earth ion dopant concentration achievable in crystalline host materials has allowed the demonstration of very high gain per unit length in an Yb 3 -doped KYWO 4 2 waveguide (∼935 dB∕cm at 980 nm) [28] and in an Er 3 -doped chloride silicate nanowire (∼100 dB∕cm at 1530 nm). However, such crystalline devices are difficult to fabricate [29] and to integrate onto a passive photonic platform for the development of more complex functionalities. Amorphous host materials can typically be deposited at the wafer level leading to simpler fabrication and integration schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous integration (e.g. bonding onto a SiO 2 substrate followed by thinning and lapping to the desired thickness) is the method primarily proposed for the realization of such high-refractive index contrast waveguides [20]. Control of the final layer thickness is the biggest challenge in this method and strategies such as a polishing stop have been proposed [21].…”
Section: Introductionmentioning
confidence: 99%
“…A refractive index contrast ranging from 0.4 to 0.6 can be achieved by the integration of KY(WO 4 ) 2 onto a glass substrate. Sefünç et al have demonstrated the integration of KY(WO 4 ) 2 on a glass substrate, using room-temperature curable adhesive (NOA81) and an extensive lapping and polishing procedure to thin a bulk crystal from 1 mm down to 2.4 µm [20]. Waveguides with a maximum length of 300 µm were fabricated using focused ion beam (FIB) milling.…”
Section: Introductionmentioning
confidence: 99%